Cardiopulmonary resuscitation skills profile and knowledge of nurses working in an academic hospital - Rikhotso, M.; Perrie, H.; Scribante, J.; Jooma, Z. (SA Heart Journal, 2021)
Introduction and aim: Cardiopulmonary arrest can occur unexpectedly and has a high mortality. Nurses are often the first responders to in-hospital arrest and are expected to initiate cardiopulmonary resuscitation (CPR). It has been identified in the literature that nurses lack the knowledge and the skills of resuscitation. The aim of the study was to determine the CPR skills profile and knowledge among nurses in selected areas at Chris Hani Baragwanath Academic Hospital. Materials and methods: The study was descriptive, prospective and contextual. A self-administered questionnaire, based on the 2010 American Heart Association CPR Guidelines, was used to determine the nurses CPR knowledge. A minimum score of ≥80% was regarded adequate. Results: Total of 133 nurses were recruited; 61 in theatre, 40 in ICU and 32 from the surgical wards. The nurses’ median score (range) for theoretical knowledge was 21% (0% - 79%). No participant achieved ≥80%. No correlation was found between nurses’ knowledge and years of experience (r=0.036, p=0.697). Comparison between knowledge scores and area of work (p=0.060) and accreditation status (p=0.444) were not statistically significant. Conclusion: The knowledge of CPR was found to be poor among nurses and has shown the need for ongoing CPR training to ensure effective resuscitation of patients. Dedicated funding and time to train nurses in CPR should be motivated for.